Influence of Financial Literacy, Self-Control, and Risk Tolerance on Financial Well-Being with Investment Decision-Making as a Mediating Variable in Generation Z in Jambi City - Raras Aroyo; Wirmie Eka Putra; Rita Friyani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of financial literacy, self-control, and risk tolerance on the financial well-being of Generation Z in Jambi City, where low literacy and impulsive behavior threaten financial stability (OJK, 2024). The aim is to examine the direct and mediating relationships in investment decision-making. Using a quantitative explanatory approach with PLS-SEM, the Generation Z population aged 18-28 years (133,114 people) was purposively sampled to obtain 100 respondents via a Google Form questionnaire. SmartPLS analysis included validity, reliability, and hypothesis testing. The results showed that financial literacy (β=0.405, p<0.01) and self-control (β=0.391, p<0.01) had a direct significant effect on financial well-being; investment decision-making mediated partially (H8-H9 were accepted), while risk tolerance was not significant (H3, H7, H10 were rejected). The conclusion recommends a self-control-based digital literacy program to improve sustainable investment decisions.